Handel In Lampongsche Districten: International Trade in Lampung District 1867 – 1914 - Perdana, Yusuf; Sumargono, Sumargono; Pratama, Rinaldo Adi; Suroto, Suroto (Historia Madania: Jurnal Ilmu Sejarah, 2024)
This research aims to find out: 1). Lampung District International Trade 1867 – 1914, 2) Impact of Lampung District International Trade. This research uses historical or historical research methods, which consist of several steps, including: Heuristics or searching for sources collected from various sources such as archives, scientific journals, books, results of previous research as well as from national libraries and delpher.nl, next is criticism sources or examining the truth from existing sources, data interpretation, namely interpreting history, and historiography, namely describing it again in writing, so that it can be understood completely. The results of this research are 1). Lampung district at the end of the 20th century, especially in 1867, had become one part of the international trade chain. It can be seen how Lampung not only imports various commodities or goods, but the Lampung district also shows that the Lampung district participates in producing goods and exporting them to various world markets, such as coffee, pepper, cotton and so on. However, on the other hand, the Lampung district also imports or brings in various commodities needed in the Lampung district with various kinds of goods including: salt, manufacturing, furniture, salt, rice and even oil. 2). The impact of international trade itself is that the people of Lampung are introduced to various types of commodities that sell well on the world market, and education about agriculture or plantations properly and maximally from the Dutch colonial government and private parties from foreign investors.